Coyote Steals Fire : A Shoshone Tale - Northwestern Band of Shoshoni Nation of Utah (Washakie); Project Muse. (Logan, Utah : Utah State University Press, 2005)
Members of the Northwestern Band of the Shoshone Nation developed the concept for this retelling of a traditional Shoshone folktale. Together, they wrote and illustrated the book.
Coyote Steals Fire -- History, Culture, and Traditions of the Northwestern Shoshone -- Significant Events in Modern Northwestern Shoshone History -- Culture, Tradition, and Education -- Listener's Guide to the Coyote Steals Fire CD -- About the Book.
Description based on print version record.
Keywords: Coyote -- (Mythological character); Coyote -- (Mythological character) -- Legends; Shoshoni Indians; JUVENILE NONFICTION -- Social Science -- Folklore & Mythology; Shoshone (Indiens) -- Folklore; Shoshoni Indians -- Folklore; Legends; Folklore; Electronic books